2017
DOI: 10.1002/2017wr020895
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Hysteretic Dynamic Capillarity Effect in Unsaturated Flow

Abstract: The difference between average pressures of two immiscible fluids is commonly assumed to be the same as macroscopic capillary pressure, which is considered to be a function of saturation only. However, under transient conditions, a dependence of this pressure difference on the time rate of saturation change has been observed by many researchers. This is commonly referred to as dynamic capillarity effect. As a first‐order approximation, the dynamic term is assumed to be linearly dependent on the time rate of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 44 publications
(79 reference statements)
3
36
0
Order By: Relevance
“…Dynamic effects in our simulations are small (less than 5.5 Pa s) for saturation values higher than 0.82 whereas for saturation values lower than 0.82, dynamic effects barely exist (i.e., τ is close to zero). However, experimental studies typically obtain larger values of τ, for example, Zhuang et al () reported a value of τ in the range of 5 × 10 4 to 3 × 10 6 Pa s. But in experiments the sample size is larger than that of our simulations. The domain size in our model is 3.2 × 3.2 × 3.2 mm 3 whereas the sample size in experiments by Zhuang et al () was 30 × 30 × 20 mm 3 .…”
Section: Resultsmentioning
confidence: 50%
See 1 more Smart Citation
“…Dynamic effects in our simulations are small (less than 5.5 Pa s) for saturation values higher than 0.82 whereas for saturation values lower than 0.82, dynamic effects barely exist (i.e., τ is close to zero). However, experimental studies typically obtain larger values of τ, for example, Zhuang et al () reported a value of τ in the range of 5 × 10 4 to 3 × 10 6 Pa s. But in experiments the sample size is larger than that of our simulations. The domain size in our model is 3.2 × 3.2 × 3.2 mm 3 whereas the sample size in experiments by Zhuang et al () was 30 × 30 × 20 mm 3 .…”
Section: Resultsmentioning
confidence: 50%
“…To test our model, we simulated the fast drainage experiments reported by Zhuang et al (). In those experiments, fast drainage was studied for a filter sand having a particle diameter of 0.0–0.50 mm (with an average diameter of 0.20 mm) and porosity value of 0.39.…”
Section: Simulation Setupmentioning
confidence: 99%
“…The results obtained with the ESD model deviated substantially from the data, while the results from the IFA model showed much better agreement. The fitted values of L im and L dr are different from those of Zhuang et al (2017b) but have the same order of magnitude. Because L is a material property, different values may reasonably be expected for different sands.…”
Section: Resultsmentioning
confidence: 70%
“…For example, it is not clear what the importance of various terms are and how the various material coefficients should be determined experimentally. Also, to our knowledge, only two studies exist where the interfacial area model has been used to simulate experiments (Zhuang et al, 2016, 2017b). These two studies were both related to horizontal redistribution, which has a flow regime and experimental design that is very different from downward water infiltration studies.…”
mentioning
confidence: 99%
“…Nevertheless, during the past few decades, studies conducted under nonequilibrium conditions have indicated that the soil water retention curve may depend on the dynamics of water flow [14,15]. Water content measured under transient flow conditions has been shown to be significantly different from that measured under static and steady-state conditions [16][17][18][19][20][21]. Considering the soil water retention curve based on thermodynamics, Hassanizadeh and Gray [22], postulated the existence of a dynamic component in the unsaturated water flow.…”
Section: Introductionmentioning
confidence: 99%